Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Proyek Konstruksi Gedung di Kawasan Inti Pusat Pemerintahan Ibu Kota Negara (IKN) - Laksono, Arvidya Esta; Priyambodo, Bambang; Naibaho, Pio Ranap Tua; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The implementation of the Occupational Safety and Health Management System (SMK3) in construction projects is an absolute necessity considering the high potential risk of work accidents. This study aims to evaluate the extent to which SMK3 is implemented in the construction project of the POLRI and BIN Flats (Rusun) in the Core Area of ​​the Government Center (KIPP) of the National Capital City (IKN). The research method used is a quantitative approach by distributing questionnaires to 106 respondents consisting of project managers, supervisors, and field workers. The results of the analysis show that the average level of SMK3 implementation is in the good category (mean = 4.06 on a scale of 5). The highest indicators are in the safety culture aspect and the role of the K3 manager. However, there are still challenges in the logistics and coordination aspects across jobs. This study recommends increasing the integration of safety technology and regular training for workers.